Gender empowerment gaps in agriculture and children’s well-being in Bangladesh - Malapit, Hazel J.; Sraboni, Esha; Quisumbing, Agnes R.; Ahmed, Akhter (International Food Policy Research Institute, 2015)
Development programs that reduce gender gaps are expected to not only improve women’s well-being, but also their children’s. This draws on a growing body of literature that shows a strong positive association between women’s status and control over resources and improvements in children’s outcomes, particularly nutrition and education. In this paper, we provide empirical evidence on the relationship between empowerment gaps between men and women in the same household and children’s well-being using nationally representative data from the 2012 Bangladesh Integrated Household Survey (BIHS). We measure children’s well-being using nutritional status for younger children (ages 0–5) and education outcomes for older children (ages 6–10 and 11–17). We measure relative empowerment using direct measures of empowerment collected from men and women in the same households using the Women’s Empowerment in Agriculture Index. Our findings suggest that gender gaps in empowerment are only weakly linked to children’s nutrition, although different measures of empowerment reveal significant differences between boys’ and girls’ outcomes, depending on the measures used. Overall, the household head’s (father’s) education is significantly associated with better nutrition and education outcomes for children, but younger girls (ages 6–10) and older boys and girls (ages 11–17) are more likely to receive more education when mothers are more educated. Our results on parental education suggest that fathers’ empowerment may be reflecting a “wealth” effect that is invested in children’s nutrition and education when they are young, while mothers’ empowerment becomes more important in girls’ education in general and keeping older children, regardless of sex, in school.